PERAN GURU PJOK DALAM IMPLEMENTASI 7 KEBIASAAN ANAK INDONESIA HEBAT DI KECAMATAN TAPIN UTARA - Rajibi, Muhammad Nadjmi; Mashud, Mashud; Haffyandi, Recky Ahmad (Jurnal Porkes, 2025)
This study aims to determine and analyze the role of PJOK teachers in implementing the 7 habits of great Indonesian children in Tapin Utara District. The problem is how PJOK teachers can internalize character values. This research uses a mixed methods approach with quantitative and qualitative descriptive methods. The population in this study were all elementary and junior high school PJOK teachers in North Tapin District, with a sample of 20 teachers taken using purposive sampling technique. The instruments used were Likert scale questionnaires and interviews. Quantitative data analysis techniques were carried out descriptively statistically, while qualitative data were analyzed using an analysis model that included data reduction, data presentation, and conclusion drawing. The results showed that PJOK teachers play an important role in integrating healthy living habits and character values through physical activity, with the indicators “love to learn” and “exercise” showing the highest achievements. This research contributes to the expansion of the function of physical education as a vehicle for student character development, as well as showing the need for synergy between schools and parents. In conclusion, character education based on physical education has great potential if supported by reflective learning strategies, adequate facilities, and cross-role collaboration.